Understanding librarians communication is the issue - Hull, Barbara (Witney Chandos Publishing (Oxford) Ltd, 2011)
Aimed at professionals and trainee professionals within the library and information service (LIS) fields, this book reminds the reader of the frequently ignored communication-gulf between the professional and the layman, and in particular the lack of true communication between LIS professional and the user. It focuses especially on 'non-standard' users, such as non-native speakers or those with some disability. The author will provide accessible examples of good practice, assess their degree of success and suggest further ways to improve performance in information provision.
Keywords: Communication in library science; Interpersonal relations; Libraries and community -- Great Britain; Libraries -- Public relations -- Great Britain